Plan de gestión integral de residuos sólidos urbanos, para el Gobierno Autónomo Descentralizado Municipal del cantón Ventanas, provincia de los Ríos, año 2013 - Romero Salvatierra, Celso Javier (2013)
The Comprehensive Plan Solid Waste Management for Decentralized Autonomous Municipal Government of Guangzhou Windows, aims to be a tool to articulate, effective and efficient provision of collection, treatment and disposal of waste. The plan consists of a series of steps that must be systematized in the medium term and must be sustainable over time, and to link directly to citizens as the main actors of change, to achieve the goal of providing comprehensive management solid waste which will protect the environment, the health of the inhabitants, as well as providing an image of cleanliness and neatness of the city of Windows. The Chapter I refer to the Contextual Marco of the investigation where thought about the problem, the formulation of the problem and the objectives of the investigation, this element allowed basing the investigation with elements that allowed carrying out the outline of the proposed Strategic Plan. The Chapter II, the Theoretical Marco contains, where he has been carried out the pertinent literary investigation to the topic of the proposal; besides legal part in that the project is sustained. In the Chapter III, it contains the methodology of utilized investigation, the population and sample that served like reference to carry out the surveys to the inhabitants of the canton and the workers of the Unit of Gathering of Solid Residuals. In the Chapter IV, it corresponds to the obtained results of the surveys and the discussion that which allowed to analyze and to interpret the opinions of those interviewed, to carry out the main FODA, In the Discussion the confirmation of the Hypothesis settled down. The Chapter V corresponds to the solution proposal that based on the obtained results of the investigation, he/she thought about as alternative for the solution of the outlined problem. The Chapter VI referred to the Summations and Recommendations, based on the outlined proposal. Finally in the Chapter VI were determined the consulted bibliography and the Chapter VII the Annexes they are detailed.